A rare case of neonatal dwarfism - Question - Valentina Ibba; Manuela Gallo; Lucrezia Giua Marassi; Luisa Anedda; Maria Antonietta Marcialis; Maria Cristina Pintus (Hygeia Press di Corridori Marinella, 2022)
I. was born from a 34-year-old woman at the 35th week of gestational age, from an elective cesarean section due to premature rupture of membranes and suspected fetal malformation with polyhydramnios.  At the 28th week of gestational age, there was a first suspicion of Jeune Syndrome (asphyxiating thoracic dystrophy). At birth, the baby showed a picture of asphyxia with 4 on Apgar score. On physical examination, it was highlighted a large head with prominent frontal bones, open normotensive bregmatic fontanelle, bell-shaped chest, narrow in the upper half and flared at the base, and prominent abdomen; the limbs were shortened, curved and stocky, thighs were adducted and externally rotated, arms extended, hands and feet were small and stocky. Cutaneous and subcutaneous tissues were well represented, with evident overabundant skin folds of the limbs and at the base of the neck, which moreover was shorter than normal. A baby-gram radiography with the whole body of the newborn was performed. 1. What do you see in the baby-gram X-ray? 2. What is your diagnosis?